Comparative effects of Zumba and Yoga on stress, body satisfaction, and self-esteem in working women: a randomized control trial - Noortje Anita Kumaat; Afif Rusdiawan; Procopio B. Dafun JR.; Heri Wahyudi; Popy Elisano Arfanda; Fransisca Januarumi Marhaendra Wijaya; Himawan Wismanadi; Ary Artanty (Pedagogy of Physical Culture and Sports)
Background and Study Aim. Working women experience increased stress due to their dual roles as employees, homemakers, and family carers. This study aimed to compare the effects of Zumba and yoga on stress, body satisfaction, and self-esteem in working women.